Microcystic Mesenteric Lymphatic Malformation, a Mimicker of Solid Masses in Pediatrics - Shamim Tayebi; Masoud Mahdavi Rashed; Majid Shams; Mona Maftouh (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2020)
Mesenteric microcystic lymphangioma is a rare benign abdominal mass. It appears as a solid mass which may mimic a solid mesenteric or omental mass. Pure microcystic lesions are ill-defined and hyperechoic due to abundant wall interfaces. A case of mesenteric microcystic lymphangioma is presented in combination with appendicitis. A 6-year-old boy presented with rapid onset of abdominal pain accompanied by nausea and vomiting. Ultrasound showed a hyperechoic solid mass without vascularity at Doppler evaluation. Computed tomography showed a mass in the small bowel mesentery with attenuation values in the range of water. In the pathologic evaluation, mesenteric lymphangioma with small and medium-sized cysts was reported. Microcystic lymphatic malformation could be considered in the differential diagnosis of a solid abdominal mass in pediatrics and imaging features can be helpful to differentiate between them.